Customer Loyalty in Recreational Long-Distance Races: Differences Between Novice and Experienced Runners - Cabello-Manrique, David; Fernández-Martínez, Antonio; Roca Cruz, Antonio Francisco; García-García, Borja; Nuviala, Alberto (Frontiers in Psychology, 2021)
A growing number of recreational races are being held in different locations, drawing many local and visiting runners. This study examines the relationships between quality, value, satisfaction, and loyalty among runners in a recreational race and examines potential differences in relationships between these constructs based on the runners’ experience. The participants were 985 runners with a mean age of 40.74 ±9.41 years. Validated, reliable ad hoc instruments were used. A multi-group analysis was performed to ascertain the existence of relationships between the constructs and differences in the relationships between the different study groups. The results show that quality is a direct antecedent of value and satisfaction. Value is directly related to satisfaction and indirectly related to loyalty. Satisfaction is related to the loyalty of participants in the race. Differences in the relationship between satisfaction and loyalty were dependent upon the runners’ experience. Loyalty to a race depends primarily on satisfaction and is modified by the runners’ experience.